Endovascular Aortic Repair After Proximal Stent Graft Migration of a Modified Frozen Elephant Trunk. Issue 2 (March 2020) - Dalal, Alex R.; Pedroza, Albert J.; Iwakoshi, Shinichi; Lee, Jason T.; Fleischmann, Dominik; Watkins, A. Claire
We describe the endovascular repair for a proximal endograft migration following a modified frozen elephant trunk (mFET) repair for a retrograde type A dissection (retro-A AD). A 40-year-old man presented with a type B aortic dissection that progressed to a retro-A AD. He was emergently taken to the operating room for an mFET repair. Computed tomography (CT) angiogram on the day of discharge revealed that the proximal end of the endograft migrated through the primary intimal tear resulting in obstruction of true lumen flow. The patient returned to the catheterization lab for endovascular repair utilizing a through-and-through wire to extend the endograft proximally and a left carotid-subclavian artery bypass. This complication highlights the importance of postoperative CT surveillance and the endovascular technique utilized to restore aortic true lumen flow.